컴퓨터단층영상에서 TIA를 이용한 간경화의 컴퓨터보조진단 - 김창수(Changsoo Kim); 고성진(Seong-Jin Ko); 강세식(Se-Sik Kang); 김정훈(Jung-Hoon Kim); 김동현(Donghyun Kim); 최석윤(Seokyoon Choi) (한국콘텐츠학회 논문지, 12(4), 2012)
Cirrhosis is a consequence of chronic liver disease characterized by replacement of liver tissue by fibrosis, scar tissue and regenerative nodules leading to loss of liver function. Liver Cirrhosis is most commonly caused by alcoholism, hepatitis B and C, and fatty liver disease, but has many other possible causes. Some cases are idiopathic disease from unknown cause. Abdomen of liver Computed tomography(CT) is one of the primary imaging procedures for evaluating liver disease such as liver cirrhosis, Alcoholic liver disease(ALD), cancer, and interval changes because it is economical and easy to use. The purpose of this study is to detect technique for computer-aided diagnosis(CAD) to identify liver cirrhosis in abdomen CT. We experimented on the principal components analysis(PCA) algorithm in the other method and suggested texture information analysis(TIA). Forty clinical cases involving a total of 634 CT sectional images were used in this study. Liver cirrhosis was detected by PCA method(detection rate of 35%), and by TIA methods(detection rate of 100%-AGI, TM, MU, EN). Our present results show that our method can be regarded as a technique for CAD systems to detect liver cirrhosis in CT liver images. 간경화(liver cirrhosis)는 섬유조직의 증식과 재생성 결절 형성의 형태학적인 변화로 2차적으로 간내혈관의 변형 및 간기능의 저하가 나타나는 질병이며, 정맥류, 복수와 부종, 간성뇌증, 간암 등의 합병증 동반을 미연에 방지하는 것이 간경변증 진단 및 치료에 핵심이다. 일반적으로 간 컴퓨터단층영상이 간경변의 진단 및 병기를 결정하는 방법으로 사용한다. 그러므로 본 연구에서는 간경화의 자동 인식을 위하여 PCA와 TIA 알고리즘을 이용한 특징추출을 통하여 간경변의 자동 검출능력을 알아보고, 각 알고리즘간의 성능을 비교하였다. 실험은 학습영상과 테스트영상으로 구분한다. 고유영상을 생성시키기 위한 학습영상으로 정상영상이 사용되고, 테스트영상으로는 간경화영상이 사용된다. 간 CT 영상에서 간의 질병 부위를 균등하게 ROI 설정하고, $50{×}50$ 픽셀 크기로 영상을 저장하여 실험하였다. 실험결과로 PCA는 간경화 검출율이 35%로 질병 인식으로 부적합하며, TIA 알고리즘의 AGL, TM, MU, EN는 100% 질병 인식력을 나타내어 간경화 자동 진단 인식으로 가능했다. 또한 결과를 임상에 적용하여 간경변의 컴퓨터보조진단으로 활용한다면 영상의학과 의사에게 업무 부담을 줄이고, 일차적 간경변의 스크리닝 도구로서 활용이 가능할 것이다. 그리고 TIA 알고리즘을 활용한 자동진단은 질병 진단의 전단계로서 예비판독의 정보를 제공하며 간경변의 조기 진단 및 예방이 가능다고 판단된다.